Evaluation of the effectiveness, implementation and cost-effectiveness of the Stay One Step Ahead home safety promotion intervention for pre-school children: a study protocol. Issue 6 (16th October 2020) - Orton, Elizabeth; Watson, Michael Craig; Hayes, Mike; Patel, Tina; Jones, Matthew; Coupland, Carol; Timblin, Clare; Carpenter, Hannah; Kendrick, Denise
Abstract : Background: Unintentional injuries in children under the age of 5 years commonly occur in the home and disproportionately affect those living in disadvantaged circumstances. Targeted home safety promotion should be offered to families most at risk but there is a paucity of standardised evidence-based resources available for use across family-support practitioners. Objective: To assess the effectiveness, implementation and cost-effectiveness of a 2-year home safety programme (Stay One Step Ahead) developed by parents, practitioners and researchers, and delivered by a range of family support providers in inner-city localities, compared with usual care in matched control localities. Methods: Parents of children aged 0 to 7 months will be recruited to a controlled before and after observational study. The primary outcome is home safety assessed by the proportion of families with a fitted and working smoke alarm, safety gate on stairs (where applicable) and poisons stored out of reach, assessed using parent-administered questionnaires at baseline, 12 and 24 months. Secondary outcomes include: the impact on other parent-reported safety behaviours, medically-attended injuries, self-efficacy for home safety and knowledge of child development and injury risk using questionnaires and emergency department attendance data; implementation (reach, acceptability, barriers, facilitators) of home safety promotion assessed through interviews and observations; and cost-effectiveness using medically-attended injury costs ascertained from healthcare records. Conclusion: If shown to be effective and cost-effective this study will provide a practical resource to underpin national guidance. The study could inform public health prevention strategies to reduce home injury in children most at risk, while delivering cost savings to health and care services. Trial registration number: ISRCTN31210493 ; Pre result.